a PENGARUH BEBAN KERJA DAN LINGKUNGAN KERJA TERHADAP KEPUASAN KERJA KARYAWAN DI PT FREYJA TELEMA KONSTRUKSINDO TANGERANG SELATAN - adehadiono; Rina Zahro, Ihdynas (NIAGARA Scientific Journal, 2025)
This study aims to find out whether there is an influence of workload and work environment on employee job satisfaction at PT. Freyja Telema Konstruksindo South Tangerang. The method used is the quantitative method, using census techniques or using saturated samples. The population of this study is 120 people, all of whom are employees within PT. Freyja Telema Konstruksindo South Tangerang. The results of this study show that there is an influence of workload on job satisfaction, the results are based on hypothesis testing, namely a calculation of 5,099 > a table of 1,657 and a significance value of 0.00 < 0.05. There is an influence between work environments on job satisfaction, the results are based on hypothesis testing, namely a calculation of 9,111 > a table of 1,657 and the significance value is 0.00 < 0.05. Workload and work environment simultaneously have a positive and significant influence on job satisfaction at PT Freyja Telema Konstruksindo South Tangerang based on the anova table, job satisfaction is obtained > 2,680 and a significance value of <0.05 which is (0.00). Keywords: Workload, Work Environment, Employee Job Satisfaction